2020
DOI: 10.1088/1361-6595/ab7d8e
|View full text |Cite
|
Sign up to set email alerts
|

Resonant microwaves probing acoustic waves from an RF plasma jet

Abstract: Microwave cavity resonance spectroscopy is introduced and demonstrated as a new approach to investigate the generation of acoustic waves by a pulsed radio-frequency driven atmospheric-pressure plasma jet. Thanks to recent advancements in the diagnostic method, the lower detection limit for pressure changes in air is ∼0.3 Pa. Good agreement with conventional pressure transducer measurements with respect to the temporal evolution, the pressure amplitude and the spectral response is found. Fourier analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Please consult appendix A.2 for the specific equations used for the calculation of the (additional) electron density and the (change in) effective collision frequency caused by the discharge and the laser photodetachment events. The time-resolved measurement scheme to determine the resonance frequency and quality factor was deployed previously at atmospheric pressure to study pulsed high-voltage discharges in nitrogen [28] and RF discharges in helium interacting with ambient air [29,30]. From an experimental point of view, first, microwave power was introduced via an antenna into the cavity to excite the TM 010 resonant mode.…”
Section: Methodsmentioning
confidence: 99%
“…Please consult appendix A.2 for the specific equations used for the calculation of the (additional) electron density and the (change in) effective collision frequency caused by the discharge and the laser photodetachment events. The time-resolved measurement scheme to determine the resonance frequency and quality factor was deployed previously at atmospheric pressure to study pulsed high-voltage discharges in nitrogen [28] and RF discharges in helium interacting with ambient air [29,30]. From an experimental point of view, first, microwave power was introduced via an antenna into the cavity to excite the TM 010 resonant mode.…”
Section: Methodsmentioning
confidence: 99%
“…The resonance frequency was obtained post-measurement by fitting the reflected microwave power signal, P refl , and determining the minimum of this fit. The same approach with a moving average filter (temporal width = 1 µs) as used in [11,14] was employed here to increase the spectral resolution to 2 × 10 2 Hz.…”
Section: Data Acquisition Systemmentioning
confidence: 99%
“…The diffusive mechanisms governing the plasma decay depend, among others, on the electron mean free path and the initial plasma dimensions [9]. Recently, the sensitivity of MCRS has been increased [11][12][13][14][15], enabling the exploration of a third decay regime [11]. This provided in-depth insight into the lowdensity electron dynamics of an EUV-induced argon plasma, late in the afterglow.…”
Section: Introductionmentioning
confidence: 99%
“…Platier et al, reported the utilization of microwave cavity resonance spectroscopy to estimate the electron density and effective electron collision frequency in the spatial afterglow of a 13.56 MHz pulsed driven atmospheric pressure helium plasma jet. [ 31 ] Modulation frequency was set between 125 and 8000 Hz, and the duty cycle was varied from 40% to 0.625%, and during the “plasma on” phase, values of 1.7 ± 0.3 × 10 18 m −3 for the electron density and 0.12 ± 0.01 THz for the electron collision frequency were found. In another study, the effect of pulse modulation on the ionic content of a 13.56 MHz helium plasma needle was explored using molecular beam mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%